Hodgkin’s lymphoma in adults – diagnosis and treatment - Gruszczyńska, Anna; Kowalik, Krzysztof; Jabłońska, Dagmara; Hetman, Katarzyna; Modrzejewski, Andrzej (Family Medicine & Primary Care Review, 2024)
Hodgkin’s lymphoma (HL) is a malignant disease of the lymphatic system with two peaks of incidence. Often one of the first symptoms of the disease is non-painful enlargement of the lymph nodes. The development of diagnostic techniques has allowed more efficient evaluation of the lesions. Classification of patients according to stage and the presence of risk factors has made it possible to tailor treatment regimes to the individual patient. The article discusses the diagnosis and contemporary treatment options for HL.